2018
DOI: 10.1016/j.cmi.2017.10.034
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of travellers' diarrhoea: analysis of pathogen findings by destination in various (sub)tropical regions

Abstract: EPEC and EAEC outnumbered ETEC and Campylobacter everywhere, yet the proportions of pathogen findings varied by region, with ETEC and Campylobacter rates showing the greatest differences. The high frequency of multibacterial findings in many regions indicates a need for further investigation of the clinical role of each pathogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
4
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 29 publications
6
31
4
3
Order By: Relevance
“…This acquisition of E. coli is worrying and deserves further investigation aimed at evaluating antibiotic resistance in these bacteria, since one study conducted in medical students revealed a 35% acquisition rate of extended-spectrum beta-lactamase-producing Enterobacteriae [8]. We found no significant association between diarrhoea and E. coli carriage in our study, in contrast with other studies where EAEC has been reported to be frequently associated with diarrhoea in travellers returning from various geographical areas [25][26][27][28][29]. This may be explained either by asymptomatic colonisation or by prolonged nucleic acid shedding in the absence of viable pathogens.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…This acquisition of E. coli is worrying and deserves further investigation aimed at evaluating antibiotic resistance in these bacteria, since one study conducted in medical students revealed a 35% acquisition rate of extended-spectrum beta-lactamase-producing Enterobacteriae [8]. We found no significant association between diarrhoea and E. coli carriage in our study, in contrast with other studies where EAEC has been reported to be frequently associated with diarrhoea in travellers returning from various geographical areas [25][26][27][28][29]. This may be explained either by asymptomatic colonisation or by prolonged nucleic acid shedding in the absence of viable pathogens.…”
Section: Discussioncontrasting
confidence: 96%
“…Such high rates of EPEC in both asymptomatic medical students and an older Muslim population from Marseille at baseline warrants further investigation in different populations, to better understand the local epidemiology of EPEC in southern France. Nevertheless, we documented a dramatically high acquisition rate of EAEC (53.0%) and EPEC (41.0%) among medical students, as documented in other recent studies conducted in different populations of international travellers [25][26][27][28][29][30][31]. This acquisition of E. coli is worrying and deserves further investigation aimed at evaluating antibiotic resistance in these bacteria, since one study conducted in medical students revealed a 35% acquisition rate of extended-spectrum beta-lactamase-producing Enterobacteriae [8].…”
Section: Discussionsupporting
confidence: 79%
“…International travel is an established risk factor for diarrhoea, the most common illness afflicting travellers [27,28], afflicting approximately 50% of travellers after a 2-week travel period [29,30]. "Traveller's diarrhoea" is often attributed to bacterial infections, particularly ETEC or EAEC [31][32][33][34][35]. Most studies focus on travellers from high-income countries who tend to be more immunologically na€ ıve [31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…"Traveller's diarrhoea" is often attributed to bacterial infections, particularly ETEC or EAEC [31][32][33][34][35]. Most studies focus on travellers from high-income countries who tend to be more immunologically na€ ıve [31][32][33][34][35][36]. However, "traveller's diarrhoea" can also feasibly occur within LMIC countries, as a result of within-country travel between areas of high vs. low transmission [20].…”
Section: Introductionmentioning
confidence: 99%
“…All participants had given written informed consent. For the same volunteers, we previously reported the findings of resistant Enterobacteriacae [24,28], travel-related health problems [43], stool pathogen findings in various geographical regions [44] as well as of those 382 travellers who used no antimicrobials [18].…”
Section: Study Populationmentioning
confidence: 89%